Early selection and assessment of drought tolerance in bread wheat germplasm - Ahmed, Hafiz Ghulam Muhu-Din; Mushtaq, Muhammad Moaaz; Aziz Ullah; Zain Ul Abdeen; Ajmal, Muhammad; Rafiq, Muhammad Hamza; Usama, Ali (Journal of Pure and Applied Agriculture, 2024)
Drought can significantly impact on wheat and can lead to reduced yields, lower quality grains, increased susceptibility to pests and disease in many parts of the world. An experiment was conducted to investigate the response of 100 wheat genotypes in the seedling stage under normal and drought conditions using a Completely Randomized Design. The analysis of variances (ANOVA) showed a highly significant difference among the genotypes in all studied traits. The results of correlation displayed a positive result with all traits expect root length in normal and drought conditions. Among the genotypes namely G-217 (Chakwal-97), G-5 (Pakitan-13), G-307 (Kohsar-95), G-17 (NIFA-LALMA) and G-38 (Shahkar-13) showed highest mean values, while the genotypes namely G-301 (BARS-09), G-104 (AS-02), G-10 (AARI-2011), G-202 (Sehar-06) and G-37 (Miraj-2008) exhibited the lowest means values. The Pearson correlation results indicated that all seedling variables, except for root length under normal and drought stress, displayed high positive and significant coefficients of association. However, root length exhibited negative and non-significant association with other studied traits and its selection seems not to be promising criteria for this germplasm for drought stress. Overall results suggested that selection for chlorophyll content, shoot length, root fresh and dry weight, shoot fresh and dry weight, turgid weight and seedling dry weight at seedling stage would improve genetic gain for drought tolerance.